Assessing the impact of Methadone Maintenance Treatment (MMT) on post-release recidivism among male federal correctional inmates in Canada - MacSwain, Mary-Ann (Criminal justice and behavior, 2014)
Methadone maintenance treatment (MMT) can benefit post-release outcomes for correctional populations with opioid dependence, yet few outcome data exist for Canada. This retrospective study examined return to custody (RTC) outcomes following correctional release among three samples of male federal offenders with problematic opioid use (n = 856): offenders who continued MMT post-release (MMT-C) and offenders who discontinued MMT post-release (MMT-T) after being initiated on correctional MMT, and a non-MMT treated control group (MMT-N). MMT status was determined by community-based urinalysis; administrative data were used for outcomes. While the rate of continued MMT was lower, the MMT-C group had a 36% lower risk of RTC than the MMT-N group; RTC risk was not significantly different between the MMT-T and the MMT-N groups. Continuous MMT for correctional offenders with opioid dependence appears to be related to decreased post-release recidivism, and thus to social reintegration outcomes. Better understanding and improvement of corrections-to-community transition dynamics concerning MMT are required.